Strains arising by seismic events in the SIRGAS-CON network region - Marotta, G. S.; França, G. S.; Monico, J. F.G. [UNESP]; Fuck, R. A. (De Gruyter, 2013)
In this study, we investigate surface strains related to seismic events and their relationship with pre- and post-seismic events in Latin America, by analyzing the variation of estimated earth coordinates supplied by a geodetic network called SIRGAS-CON. Based on data provided by the USGS for the period 2000-2011, and after the Global Congruency test, we selected four events associated with unstable geodetic network points. The resulting strains were estimated based on the finite element method using networks of points considered unstable connected to neighboring points using the Delaunay triangulation. It was possible to determine the strains along with the resulting guidelines for pre- and post-seismic, considering each triangular lattice formed for analysis as a homogeneous solid body. The calculation of strains and verification of the results allowed to analyze the interactions between lithospheric plates from the contraction and extension directions between points located in different plates. Despite the association between seismic events and the strain of geodetic network, some events of magnitude greater than 5.8 Mw were excluded because it does not show (provide) the surface strain, which is located at great depths. It was confirmed that events of greater magnitude provide increased surface strain rate when compared with other similar depths.
Keywords: geodetic network; lithospheric plates; post-seismic; pre-seismic; surface strains